Antihyperglycemic activity of tinocrisposide by stimulating 3t3-L1 adipocyte cell differentiation - Adnan, Adek Zamrud; Bakhtiar, Muhammad Taher; ,, Annisa Fauzana; Afriani, Tika; Roesma, Dewi Imelda; Putra, Andani Eka (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study is to investigate the antihyperglycemic activity of tinocrisposide by stimulating 3T3-L1 adipocyte cell differentiation. Tinocrisposide is a furanoditerpene glycoside that was isolated from Tinospora crispa (Menispermaceae). Methods: Adipocyte cell differentiation activity of tinocrisposide in interval concentrations of 50, 25, 12.5, and 6.25 µg/ml has been investigated on 3T3-L1 cell line using insulin of 1 µg/ml as a positive and Dulbecco’s modified Eagle media (DMEM) as a negative control group. The effect of tinocrisposide was quantified with oil red O staining method by measuring an absorbance of lipid solution in isopropanol at a wavelength (λ) of 520 nm. Results: Tinocrisposide in the concentrations of 50, 25, 12.5, and 6.25 µg/ml insulin of 1 µg/ml and DMEM groups showed absorbance value of 0.7669, 0.7253, 0.6563, 0.6481, 0.954, and 0.2653, respectively. It was found that there was a significant difference statistically in lipid droplets accumulation among all groups (p<0.05) and tinocrisposide at a concentration of 50 µg/ml showed the highest lipid droplets accumulation in 3T3-L1 adipocyte cells. Conclusion: From the study, it could be concluded that tinocrisposide was able to stimulate the differentiation of adipocyte cell and had antihyperglycemic activity